2005
DOI: 10.1097/01.mlg.0000163539.97485.f4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aspirin and Low-Dose Heparin in Head and Neck Reconstruction using Microvascular Free Flaps

Abstract: The free flap survival rate in patients undergoing head and neck reconstruction using this simple anticoagulation regimen of aspirin and SQH appears to be equivalent to the free flap survival rate in patients using other anticoagulation agents. In addition, aspirin and SQH do not increase the incidence of postoperative hematoma when compared with the other anticoagulation agents. Therefore, aspirin and SQH appear to be reliable postoperative anticoagulation agents for patients undergoing head and neck reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 17 publications
6
128
1
1
Order By: Relevance
“…In patients undergoing head and neck procedures and particularly free tissue transfer, the threshold for returns to the operating room to treat postoperative bleeding tends to be lower because of concerns over microvascular thrombosis and flap failure. 16,17,26 As a consequence, the rate of bleeding complications is higher. While our study suggests that chemoprophylaxis reduces the incidence of VTE in high-risk patients, the effect of chemoprophylaxis on bleeding outcomes is less clear because other risk factors for bleeding confound the analysis.…”
Section: Bleeding Complicationsmentioning
confidence: 99%
“…In patients undergoing head and neck procedures and particularly free tissue transfer, the threshold for returns to the operating room to treat postoperative bleeding tends to be lower because of concerns over microvascular thrombosis and flap failure. 16,17,26 As a consequence, the rate of bleeding complications is higher. While our study suggests that chemoprophylaxis reduces the incidence of VTE in high-risk patients, the effect of chemoprophylaxis on bleeding outcomes is less clear because other risk factors for bleeding confound the analysis.…”
Section: Bleeding Complicationsmentioning
confidence: 99%
“…In our study, we found that preoperative aspirin administration was not enough to reduce thrombosis alone and, this result was similar to previous one. On the other hand, Chien et al (2005), [9] also showed that oral aspirin and IV heparin administration had not more effective than the other treatment regimens on thrombosis in microvascular free flaps using for head and neck reconstruction. Our results indicate that this combination has litlle effects on preventing thrombosis in the gluteus maximus flaps.…”
Section: Discussionmentioning
confidence: 99%
“…However, perioperative anticoagulation with intravenous heparin showed no clinical benefit 40 . Aspirin seems to be as effective as subcutaneous heparin in free flap surgery 41 . Clopidogrel reduces microvascular thrombosis in rats, but has not been used in large numbers in clinical practice 42 .…”
Section: Coagulation and Thrombolysismentioning
confidence: 97%
“…Aspirin and low molecular weight heparin seems to be an appropriate choice of anticoagulant agents in the postoperative period of head and neck free flap reconstruction surgery 41 .…”
Section: Postoperative Periodmentioning
confidence: 99%